Mediation of Divorce Disputes by Village Governments from the Perspective of Progressive Legal Theory: Study of Effec-tiveness and Implementation in Banra'as Village, Sumenep Regency - Mawardi Mawardi; Roibin Roibin; Musleh Harry (International Journal of Law and Society, 2026)
The increasing rate of divorce in rural areas indicates serious challenges in maintaining family resilience as well as the limited effectiveness of formal litigation-based dispute resolution. Judicial processes that tend to be procedural, time-consuming, and focused on legal termination often fail to address the substantive justice needs of the disputing parties. Consequently, alternative dispute resolution mechanisms that are more responsive to local social and cultural values are required. This study aims to examine the effectiveness and implementation of divorce mediation facilitated by the Village Government of Banra’as, Sumenep Regency, through the perspective of Progressive Legal Theory. This research employs a qualitative approach with an empirical research design. Data were collected through field observations, in-depth interviews with village officials, community leaders, and individuals who had previously participated in the mediation process, as well as documentation related to divorce dispute resolution practices at the village level. Data analysis was conducted using a descriptive-analytical method, focusing on mediation practices as a manifestation of living law within the community. The findings reveal that divorce mediation facilitated by the village government demonstrates a relatively high level of effectiveness in reducing divorce cases. This effectiveness is influenced by a familial approach, the utilization of local wisdom, and the strong internalization of religious values within the social life of the Banra’as community. From the perspective of Progressive Legal Theory, this mediation practice reflects a flexible and non-positivistic understanding of law that prioritizes humanity and substantive justice. Village-based mediation not only serves as an alternative dispute resolution mechanism but also functions as a social instrument to preserve family harmony and strengthen social resilience in rural communities.